Cross-phenotype association mapping of the MHC identifies genetic variants that differentiate psoriatic arthritis from psoriasis. Issue 10 (18th August 2017) - Bowes, John; Ashcroft, James; Dand, Nick; Jalali-najafabadi, Farideh; Bellou, Eftychia; Ho, Pauline; Marzo-Ortega, Helena; Helliwell, Philip S; Feletar, Marie; Ryan, Anthony W; Kane, David J; Korendowych, Eleanor; et al.
Abstract : Objectives: Psoriatic arthritis (PsA) is a chronic inflammatory arthritis, with a strong heritable component, affecting patients with psoriasis. Here we attempt to identify genetic variants within the major histocompatibility complex (MHC) that differentiate patients with PsA from patients with cutaneous psoriasis alone (PsC). Methods: 2808 patients with PsC, 1945 patients with PsA and 8920 population controls were genotyped. We imputed SNPs, amino acids and classical HLA alleles across the MHC and tested for association with PsA compared to population controls and the PsC patient group. In addition we investigated the impact of the age of disease onset on associations. Results: HLA-C*06:02 was protective of PsA compared to PsC (p=9.57×10 −66, OR 0.37). The HLA-C*06:02 risk allele was associated with a younger age of psoriasis onset in all patients (p=1.01×10 −59 ). After controlling for the age of psoriasis onset no association of PsA to HLA-C*06:02 (p=0.07) was observed; instead, the most significant association was to amino acid at position 97 of HLA-B (p=1.54×10 −9 ) where the presence of asparagine or serine residue increased PsA risk. Asparagine at position 97 of HLA-B defines the HLA-B*27 alleles. Conclusions: By controlling for the age of psoriasis onset, we show, for the first time, that HLA-C*06:02 is not associated with PsA and that amino acid position 97 of HLA-B differentiates PsA from PsC. This amino acid also represents the largest genetic effect for ankylosing spondylitis, thereby refining the genetic overlap of these two spondyloarthropathies. Correcting for bias has important implications for cross-phenotype genetic studies.